Evolution of vertebrate genome organisation - McLysaght, Aoife (Trinity College (Dublin, Ireland). Department of Genetics, 2002)
The increasing availability of genomic sequences from different vertebrate organisms affords molecular biologists the opportunity to thoroughly investigate phenomena that were only hinted at by more sparse data. The work described in this thesis develops the use of inter-and intra-genomic sequence comparisons to examine genome evolution through changes in genome arrangement and content. The vertebrate Fugu rubrupies (pufferﬁsh) has a small genome with little repetitive sequence which makes it attractive as a model genome. Its genome compaction and synteny conservation relative to the human genome were studied using data from public databases. The compaction of this genome was measured by comparing lengths of orthologous Fugu and human introns. Analysis of orthologous introns showed an eight-fold average size reduction in Fugu, consistent with the ratio of total genome sizes. There was no consistent pattern relating the size reduction in individual introns or genes to gene base composition in either species. For genes that are neighbours in Fugu, 40-50% have conserved synteny with a human chromosome. Comparison of observed data to computer simulations suggests that 4,000-16,000 chromosomal rearrangements have occurred since Fugu and human shared a common ancestor, implying a faster rate of rearrangement than seen in human/mouse comparisons. Intragenomic comparisons were used to examine the draft human genome sequence for evidence of ancient genomic duplications, by a combination of a map-based and a phylogeny-based approach. Evidence was found for extensive paralogy regions situated throughout the genome. Statistical analyses of these regions indicated that they were formed by en bloc duplication events. Molecular clock analysis of 191 gene families in the human genome indicates that a burst of gene duplication activity took place approximately 333-583 Mya, spanning the estimated time of origin of vertebrates (about 500 Mya). Moreover, more gene pairs of this age are found in paralogous regions than pairs that duplicated earlier or later. These results support the contention that many vertebrate gene families were formed by extensive duplication events, perhaps polyploidy, in an early chordate, and indicate that extensive genome rearrangement may have occurred following genome duplication.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin